"Mistakes are just information": A case study of a highly successful violin pedagogue. (February 2022) - Blackwell, Jennifer
This study examined the instructional context, pedagogical techniques, interpersonal dynamics, and personal characteristics of a teacher and her collegiate students in a renowned private violin studio. Through lesson observations, interviews, and analysis of artifacts, the following themes emerged: (1) a nurturing, non-judgmental environment, characterized by "neutral" teacher feedback; (2) clearly defined learning expectations, lesson structure, and work habits that are mutually understood by student and teacher; (3) a clear emphasis on learning to practice effectively in the student's own time, including "practicing practicing" within the lesson; and (4) explicit instruction on how to teach others. Analysis of the data suggests that this studio might be best understood through Bruner's conception of a spiral curriculum, as the structure and content of all student lessons were virtually the same regardless of student level, but the complexity of the tasks increases greatly as students progress.